Ensuring the Rights of Vulnerable Groups in the Legislative Process in Vietnam - Uyen To Doan; Hung Manh Chu (Advanced Studies on Socio-Economy Development, 2022)
In recent years, Vietnam has actively and vigorously developed and strengthened law enforcement and facilitated access to the law to protect human rights and legitimate interests. After formulating the Judicial Reform Strategy and implementing the law, the State has created favourable conditions for vulnerable groups to participate in Vietnam's political, social, economic, and cultural life. However, it still faces challenges in ensuring and facilitating access to the law and raising legal awareness. In particular, women, ethnic minorities, people with disabilities, and children are the most vulnerable groups. Therefore, this article focuses on the guarantee of the rights of vulnerable groups in the process of law-making in Vietnam today to unveil difficulties and limitations; on that basis, it makes proposals for ensuring the rights of vulnerable groups in the legislative process in the coming time. Keywords: Human Rights, Rights of Vulnerable Groups, Law-making